Co-management of the Acaú-Goiana Extractive Reserve: Analysis of 15 years of progress and obstacles: Co-management of the Acaú-Goiana Extractive Reserve: Analysis of 15 years of progress and obstacles - Gomes de Oliveira, João Paulo (Revista Desenvolvimento Social, 2023)
This article presents a qualitative literature review of the Marine Extractive Reserve Acaú-Goiana, established in 2007 with the purpose of promoting sustainable and collective use of natural resources by fishing communities in the states of Paraíba and Pernambuco. The objective of this study is to analyze the co-management of the Acaú-Goiana Extractive Reserve after 15 years of its establishment (2007-2022), highlighting its progress and challenges. The results have identified various obstacles to co-management, including the extensive territorial expanse of the reserve, the shortage of human and financial resources of the Chico Mendes Institute for Biodiversity Conservation - ICMBio, the impacts caused by activities of agro-industrial sectors, distilleries, and cement industries in proximity to the area, as well as conflicts related to overexploitation of fishing resources and degradation of water resources. In light of this, the review emphasizes the importance of fostering continuous social participation in all decision-making processes, adapting co-management instruments and tools to the local reality, and taking into account the communities' history, traditional management practices, local culture, and forms of social organization of the beneficiaries. Furthermore, the development of a management plan for the Acaú-Goiana Extractive Reserve is deemed crucial to facilitate the organization and participation of beneficiary communities in co-management.